Amil Zakat Menurut Hukum Islam dan Peraturan Perundang-Undangan
Amil zakah (zakah manager/distributor) is one of supporting pillars to the success of zakah management. From juridical view, it is related to Islamic law, but politically it is close to the state policy especially the zakah management policy. The involvement of the state in zakah management depends on the fundamental issue that makes zakah as part of qad